2023
DOI: 10.1186/s12917-023-03689-y
|View full text |Cite|
|
Sign up to set email alerts
|

Attenuation of pathogenesis of Eimeria stiedae sporulated oocysts using Egyptian alginate propolis nanoparticles

Ahmed G. Hegazi,
Eman E. El Shanawany,
Asmaa S. El-Houssiny
et al.

Abstract: Background Coccidiosis is a costly and widespread infectious disease that affects mammals and causes huge losses for the global rabbit meat industry. This study evaluated the potency of Egyptian alginate propolis nanoparticles (NPs) in attenuating the infectivity of Eimeria stiedae sporulated oocysts. The gelification method was used to prepare alginate propolis NPs, which were then characterized using a transmission electron microscope and zeta potential analysis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…Then, substrate (100 ìl/well) (Ortho-phenylenediamine) was added, and finally the absorbance values were read in ELISA reader (ELX 800TM microplate reader) at 450nm. The cutoff point of optical density values was determined as described by El Shanawany et al ( 2019) and Hegazi et al (2023).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Then, substrate (100 ìl/well) (Ortho-phenylenediamine) was added, and finally the absorbance values were read in ELISA reader (ELX 800TM microplate reader) at 450nm. The cutoff point of optical density values was determined as described by El Shanawany et al ( 2019) and Hegazi et al (2023).…”
Section: Enzyme-linked Immunosorbent Assay (Elisa)mentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified the following errors in the in the published version. There are errors during the production process in the result section of this article such as Fig.…”
mentioning
confidence: 99%